USM TO HOLD OPEN DAY IN MAIN CAMPUS PENANG AND HEALTH CAMPUS KELANTAN - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 7 April 2016 Universiti Sains Malaysia (USM) will hold an open day programme for two days, 9 – 10 April 2016 at Dewan Utama Pelajar (DUP), Main Campus in Penang and at Dewan Utama, Health Campus, Kubang Kerian, Kelantan from 9.00 a.m. to 5.00 p.m.